Usefulness of Succinate dehydrogenase B (SDHB) immunohistochemistry in guiding mutational screening among patients with pheochromocytoma‐paraganglioma syndromes. Issue 11 (16th April 2014) - Pai, Rekha; Manipadam, Marie Therese; Singh, Pradyumn; Ebenazer, Andrew; Samuel, Prasanna; Rajaratnam, Simon
<x xml:space="preserve">Abstract</x> Genetic testing of pheochromocytomas (PCC) and paragangliomas (PGL), although expensive, is gradually becoming a part of the routine laboratory investigation for patients with PCC‐PGL syndrome. Recently, Succinate dehydrogenase B (SDHB) immunochemistry has been shown to be an excellent indicator of germline mutations in the SDH genes and could help significantly reduce cost. This study assesses the utility of SDHB immunohistochemical analysis when used to guide genetic analysis, with emphasis on cost benefits it could provide in a resource‐limited setting. Forty‐four cases of PCC/PGL characterized by genetic analysis were included to determine their SDHB expression pattern by immunohistochemistry. SDHB antibody expression was negative among three cases each, with SDHB and SDHD mutations. Immunohistochemistry results were positive for all three cases of RET, a single case of neurofibromatosis and for two cases with Von Hippel‐Lindau (VHL) mutations while the remaining two cases with VHL mutations showed a diffuse 'cytoplasmic blush'. Thirty of the remaining 31 samples demonstrated positive staining and were negative for mutations, while a lone sample that was negative for staining and mutation was not included in the final analysis as the internal control for the sample was not adequately stained. Cost analysis in our settings showed that triaging with SDHB immunohistochemistry could potentially reduce costs by USD 320–500 per patient. SDHB immunohistochemistry, when used as a guide to genetic testing, can significantly reduce the effort, time and costs of testing among patients with PCC‐PGL, a huge benefit in resource limited settings.